PENGARUH PENGELOLAAN SAMPAH DIGITAL MELALUI APLIKASI WAMS (WASTE MANAGEMENT SISTEM) DALAM MENUMBUHKAN KARAKTER PEDULI LINGKUNGAN PADA DIRI SISWA SEKOLAH DASAR DI KOTA SERANG - Suhendi; Tito Parta Wibowo; Arif Hidayat; Iin Kurnia; Dwi Saktiawan; Setiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of digital waste management through the WAMS (Waste Management System) application in fostering environmental care character among elementary school students in Serang City. The increasing waste problem demands technology-based management innovations capable of building environmental awareness from an early age. The WAMS application is utilized as a digital waste management medium that facilitates students in sorting, recording, and monitoring waste management activities effectively and educationally. This research employed a quantitative approach using a survey method. The subjects of the study were elementary school students in Serang City who participated in the use of the WAMS application in school waste management activities. Data collection techniques included questionnaires, observations, and documentation. The data were analyzed using descriptive and inferential statistical analysis to determine the level of influence of the application on the development of students’ environmental care character. The results showed that digital waste management through the WAMS application had a positive and significant effect on the environmental care character of elementary school students. Students demonstrated increased awareness in maintaining environmental cleanliness, proper waste sorting habits, and responsibility toward the school environment. Therefore, the WAMS application can serve as an innovative alternative in supporting environmental character education in elementary schools.